The prevalence of symptoms and risk factors associated with obstructive sleep apnea among patients attending primary health centers in Erbil, Iraq - Abdul-Majeed, Hana Hoshmand; Dauod, Ali Shakir (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: Although snoring and day time tiredness and are a common finding in persons with obstructed sleep apnea; however, most of them are unaware of their diseases. This study aimed to find the prevalence of sleep apnea and symptoms at the primary care level. Methods: A cross-sectional study was conducted among randomly selected 500 patients aged ≥ 18 years attending two primary care centers in Erbil city, from the 1st of April 2018 to the end of February 2019. A Berlin modified questionnaire was used to address an individual’s characteristics, risk factors, and clinical symptoms. Results: The mean age + SD of 500 individuals was 41.06 + 14.79 years. Nearly all (97.2%) of the participants were living in urban areas. Around three quarters (72.2%) of the sample were married, 27.8% were smokers, 45.8% were overweight, and 18.6% were obese. The overall prevalence of obstructed sleep apnea was 23.2%, the prevalence of low-risk OSA was 22.4%, and the prevalence increased with age. Obstructed sleep apnea was more among females (26%) than males (20.8%), although the difference was not significant. A high percentage was observed among those with raised blood pressure and obese persons (87.9% and 86%, respectively). No significant association was detected between obstructed sleep apnea and smoking. Conclusion: High risk of obstructive sleep apnea was common among patients attending primary care. Awareness and education of physicians and patients about the disease is essential. Those at high risk should be referred to sleep centers for further evaluation.